1942
DOI: 10.6028/jres.028.012
|View full text |Cite
|
Sign up to set email alerts
|

Tensile elastic properties of nickel, copper, open-hearth iron, and typical steels

Abstract: From stress-set curves are derived proof stresses for five values of permanent set. From corrected stress-strain curves are derived values of the modulus at zero stress and its stress coefficient. The diagrams show the influence of prior plastic extension on these indices.The curves of variation of the proof stresses with plastic extension are affected by the rate of work-hardening, by variation of internal stresses of two kinds, and by the rest interval. The curves of variation of the modulus of elasticity wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1942
1942
1944
1944

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The present investigation has not advanced sufficiently to warrant an explanation of the underlying cause of the reversals observed. However, the work of Wood [12] and McAdam and Mebs [13] may be significant in this connection. Wood demonstrated that continuous rolling of metals, particularly of copper, causes an increase in diameter of their X-ray diffraction rings to a maximum, following which there is a diminution to a minimum, the two processes alternating on further cold-working.…”
Section: -Influence Of Cold-rolling On the Surface Indentation Hardnementioning
confidence: 99%
“…The present investigation has not advanced sufficiently to warrant an explanation of the underlying cause of the reversals observed. However, the work of Wood [12] and McAdam and Mebs [13] may be significant in this connection. Wood demonstrated that continuous rolling of metals, particularly of copper, causes an increase in diameter of their X-ray diffraction rings to a maximum, following which there is a diminution to a minimum, the two processes alternating on further cold-working.…”
Section: -Influence Of Cold-rolling On the Surface Indentation Hardnementioning
confidence: 99%